WHAT FACTORS ARE IMPORTANT WHEN DECIDING TO ADOPT THE EVIDENCE-BASED TRANSITIONAL CARE MODEL (TCM)?. (11th November 2018) - Hirschman, K B; Yu, Z; Pennock, M J; Pepe, K; Rouse, W; Pauly, M V; Naylor, M D
Abstract: The Transitional Care Model (TCM) has been rigorously tested in multiple clinical trials but the adoption of this EBI has been one system at a time. The purpose of the first study was to describe key themes important to the decision to adopt the evidence-based interventions (EBIs) and, more specifically, the Transitional Care Model (TCM). A National Advisory Committee (NAC) with representation from providers, payers (public and private) and purchasers were interviewed and transcripts were analyzed using conventional content analyses. Key factors influencing decision making included: 1) the view that "my population" is different; 2) the central role of incentives (specifically payment); 3) beliefs about the value of evidence; and 4) the influence of peers. Factors influencing decision making to adopt EBIs such as the TCM are multidimensional. Understanding the perspectives of decision makers (i.e., providers, payers, and purchasers) is essential to promote adoption of EBIs such as the TCM.